New yeast isolate Pichia caribbica synthesizes xylolipid biosurfactant with enhanced functionality - Joshi-Navare, Kasturi; Singh, Pradeep Kumar; Prabhune, Asmita (European Journal of Lipid Science and Technology, 2014)
Sophorolipids (SL) belong to a class of glycolipidic biosurfactants suitable for a wide range of applications. The structural diversity in SL gives rise to variation in physicochemical and biological properties. To achieve the less explored head group diversity in sophorolipid structure, a new xylose fermenting yeast Pichia caribbica has been employed for biosurfactant production. The media and fermentation parameters have been optimized to achieve maximum yield of 7.48 g/L. The physicochemical properties of the xylolipid biosurfactant have been assessed. It reduced the surface tension of distilled water from 70 to 35.9 mN/m with the low critical micellar concentration (CMC) 1.0 mg/L as compared to typical SL (reported CMC range 40-100 mg/L). Structural characterization was done using FTIR and HR-MS to identify the structure. 17-L-[(beta-D-xylopyranosyl)-oxy]-Delta 9-heptadecanoic acid correlated to m/z 415 majorly constituted the product. Control experiment was performed in which glucose was provided as the hydrophilic carbon. This product was also subjected to HR-MS analysis to determine its chemical nature and found to be different from xylolipid. Presence of xylose as head group was anticipated to give altered physicochemical and biological activities and indeed a low CMC value and better inhibitory action was demonstrated against Staphylococcus aureus. Practical applications: Sophorolipids produced by microbial sources have several advantageous properties over commercial petroleum-based surfactants including biodegradability, environmentally friendly nature, and low toxicity. Here, we have attempted to modify the hydrophilic head group by incorporating xylose in place of glucose. This molecule will also behave differently in response to different stimuli. Stimuli-responsive surfactants are a class of compounds with applications in stabilization of emulsions, suspensions or foams, drug encapsulation and delivery, hard-surface cleaning, personal care applications.
Keywords: Antibacterial action; Critical micelle concentration; Pichia caribbica; Sophorolipid; Xylolipid